2017
DOI: 10.2135/cropsci2016.06.0482
|View full text |Cite
|
Sign up to set email alerts
|

Cool‐Season Turfgrass Germination and Morphological Development Comparisons at Adjusted Osmotic Potentials

Abstract: One of the major factors limiting seed germination and seedling development in a low‐input, low‐maintenance environment is soil moisture availability, yet little is known about the germination response of cool‐season turfgrasses to differing osmotic potentials. Controlled‐environment studies were conducted to identify germination characteristics of cool‐season turfgrass species experiencing water‐restricted conditions. At osmotic potentials between 0.0 and −1.6 MPa, perennial ryegrass (Lolium perenne L.) germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Accordingly, PL and RL provide an important instance whereby plants can be studied in how they respond to environmental stress (Mickky and Aldesuquy, 2017). The strongest possibility to grow in arid and saline areas occurs for plants that can maintain a longer plumule and radicle when exposed to stress conditions (Goatley et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, PL and RL provide an important instance whereby plants can be studied in how they respond to environmental stress (Mickky and Aldesuquy, 2017). The strongest possibility to grow in arid and saline areas occurs for plants that can maintain a longer plumule and radicle when exposed to stress conditions (Goatley et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…had better germination and survival rates than Kentucky bluegrass cultivars when exposed to brief moist intervals between periods of drought. Goatley, Hensler, and Askew (2017) also reported higher germination of strong creeping red fescue, Chewings fescue, and hard fescue than Kentucky bluegrass under low osmotic potentials. The calculated osmotic potential that resulted in a 50% reduction in seed germination was significantly lower for all three fine fescues than Kentucky bluegrass but higher than both perennial ryegrass and tall fescue (Goatley et al., 2017).…”
Section: Establishmentmentioning
confidence: 90%
“…Goatley, Hensler, and Askew (2017) also reported higher germination of strong creeping red fescue, Chewings fescue, and hard fescue than Kentucky bluegrass under low osmotic potentials. The calculated osmotic potential that resulted in a 50% reduction in seed germination was significantly lower for all three fine fescues than Kentucky bluegrass but higher than both perennial ryegrass and tall fescue (Goatley et al., 2017). Similarly, Larsen, Bailly, Côme, and Corbineau (2004b) reported slender creeping red fescue seeds were able to germinate at lower water potentials than Kentucky bluegrass at different temperatures.…”
Section: Establishmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Tarasoff, Ball, and Mallory-Smith (2007) also observed a decline in the germination rate of Kentucky bluegrass from 60% to 0% as osmotic potential of the solution surrounding the seeds was lowered from 0 to -2 MPa. Using increasing concentrations of D-mannitol, Goatley, Hensler, and Askew (2017) demonstrated that 'Appalachian', 'Front Page', and 'Liberator' germination was inhibited at water potentials below…”
Section: Salt Tolerance and Roadside Evaluationsmentioning
confidence: 99%